Organic anion transporter 2 transcript variant 1 shows broad ligand selectivity when expressed in multiple cell lines - Adam G Hotchkiss; Liam eBerrigan; Ryan M Pelis (Frontiers Media S.A., 2015)
Organic anion transporter 2 (OAT2) is likely important for renal and hepatic drug elimination. Three variants of the OAT2 peptide sequence have been described - OAT2 transcript variant 1 (OAT2-tv1), OAT2 transcript variant 2 (OAT2-tv2) and OAT2 transcript variant 3 (OAT2-tv3). Early studies helping to define the ligand selectivity of OAT2 failed to identify the variant used, and the studies used several heterologous expression systems. In preliminary studies using OAT2-tv1, we failed to observe transport of several previously identified substrates, leading us to speculate that ligand selectivity of OAT2 differs with variant and/or heterologous expression system. The purpose was to further investigate the ligand selectivity of the OAT2 variants expressed in multiple cell types. We cloned OAT2-tv1 and OAT2-tv2, but were unsuccessful at amplifying mRNA for OAT2-tv3 from human kidney. OAT2-tv1 and OAT2-tv2 were individually expressed in human embryonic kidney (HEK), Madin-Darby Canine Kidney (MDCK) or Chinese hamster ovary (CHO) cells. mRNA for OAT2-tv1 and OAT2-tv2 was demonstrated in each cell type transfected with the respective construct, indicating their expression. OAT2-tv1 trafficked to the plasma membrane of all three cell types, but OAT2-tv2 did not. OAT2-tv1 transported penciclovir in all three cell types, but failed to transport para-aminohippurate, succinate, glutarate, estrone-3-sulfate, paclitaxel or dehydroepiandrosterone sulfate - previously identified substrates of OAT2-tv2. Not surprising given its lack of plasma membrane expression, OAT2-tv2 failed to transport any of the organic solutes examined, including penciclovir. Penciclovir transport by OAT2-tv1 was sensitive to large (e.g., cyclosporine A) and small (e.g., allopurinol) organic compounds, as well as organic anions, cations and neutral compounds, highlighting the multiselectivity of OAT2-tv1. The potencies with which indomethacin, furosemide, cyclosporine A and cimetidine inhibited OAT2-tv1 are in good agreement with previous studies using this variant, but inconsistent with studies using OAT2 with an unidentified sequence. This study shows that organic molecules with diverse physicochemical properties interact with OAT2-tv1, making it a likely site of drug interactions. Many previously identified substrates of OAT2 are not transported by OAT2-tv1, suggesting that variant and/or expression system may contribute. Future work should establish the expression pattern and ligand selectivity of OAT2-tv3.